Life after life : a novel - McCorkle, Jill, 1958- (Algonquin Books of Chapel Hill, 2013)
The residents, staff, and neighbors of the Pine Haven retirement center (from twelve-year-old Abby to eighty-five-year-old Sadie) share some of life's most profound discoveries. What they eventually learn about themselves and one another will transform them all.